Risk Management in Agricultural Financing: Evidence from BMT Assalam Demak, Indonesia - Kusrini, Eni; Kirom, Cihwanul (IAIN Kudus, 2026)
Demak Regency is predominantly an agricultural region, yet farmers often face significant capital constraints in cultivating their rice fields, which can delay harvests or even cause crop failure. Baitul Maal wa Tamwil (BMT) Assalam Demak addresses this need by offering agricultural financing repayable at harvest time. However, limited funds mean some farmers struggle to meet the monthly installments required by BMT Assalam Demak, creating a research gap this study seeks to address. This research aims to analyze the risk management practices implemented by BMT Assalam Demak in its agricultural financing scheme, with the broader goal of helping farmers gain more systematic knowledge of agricultural financing to improve productivity and income. A qualitative method was employed, using primary data obtained from informants at BMT Assalam and secondary data from related literature, supported by data collection, validity testing, and analysis techniques. The findings show that BMT Assalam Demak effectively manages financial risks affecting both the institution and its farmer-customers, including through systematic hazard identification, competent staff, and bookkeeping software that streamlines operations. With ten branch offices across Demak Regency, BMT Assalam Demak provides farmers convenient access to financing and to tracking their financing history. The harvest-based installment scheme allows farmers to obtain loans more easily and repay them once their harvest is sold, while BMT Assalam Demak benefits through profit-sharing. This mutually beneficial relationship underscores the importance of sound risk management in sustaining both farmer welfare and institutional trustworthiness.